Sintering of synthetic barytocalcite BaCa(CO3)2, kutnahorite CaMn(CO3)2 and rhodochrosite MnCO3 for carbon-14 sequestration. Issue 1 (January 2015) - Massoni, Nicolas; Le Gallet, Sophie; Hoffmann, Stefan; Launeau, Patrick; Grin, Yuri; Bernard, Frederic
Abstract This paper reports the sintering behavior of synthetic inorganic carbonates chemically identical to barytocalcite (BaCa(CO3)2, 8.1 wt.% C), kutnahorite (CaMn(CO3)2, 11.1 mass% C) and rhodochrosite (MnCO3, 10.5 wt.% C) for 14C immobilization. As carbonates are time–temperature dependently subjected to decarbonation due to the loss of carbon dioxide, spark plasma sintering (SPS) appeared to be the most suitable method for the study. It was shown that densification and decarbonation are overlapping phenomena for kutnahorite and rhodochrosite, lowering the carbon final content, whereas barytocalcite was successfully densified without carbon loss. Barytocalcite pellets of 30 mm diameter with a relative density of 92% and a carbon content of 7.78 ± 0.28 wt.% were obtained. The study highlighted the role of sintering pressure in carbon dioxide volatilization.